The ethanolic extract of Salvia lachnostachys Benth is not maternotoxic, does not alter reproductive performance, but has teratogenic potential - Hudman Cunha Ortiz; Silvia Cordeiro das Neves; Cândida Aparecida Leite Kassuya; Henrique Rodrigues Scherer Coelho; Allana C. F. Martins; Marcelo Luiz Brandão Vilela; Valter Aragão do Nascimento; Arunachalam Karuppusamy; Maria Élida Alves Stefanello; Rodrigo Juliano Oliveira; Roberto da Silva Gomes (BMC, 2023)
Abstract Salvia lachnostachys Benth is native to Brazil and has anti-inflammatory, anti-arthritic, cytotoxic, antitumor, and antihyperalgesic activities. The population, including pregnant women, consume this plant to treat pain, inflammation, flu, spasms, insomnia, and depression, mainly. There are no safety reports on the use of this plant during pregnancy. The present study aimed to evaluate the effects of S. lachnostachys ethanolic extract (EESl) on reproductive performance, embryofetal development, and DNA integrity of pregnant female mice. Pregnant females were randomly divided into three experimental groups (n = 10): The Control group was treated with a vehicle, and treatment groups were administered with EESl at 100 and 1000 mg/kg, respectively. Treatment occurred by gavage throughout the gestational period until day 18. Afterward, reproductive performance, embryofetal development, and DNA integrity parameters were evaluated. The results indicated that EESl did not alter any reproductive performance parameters. However, it changed embryofetal outcome through reduced placental weight (EESl 100 mg/kg), decreased fetal weight (EESl 100 and 1000 mg/kg), and increased frequency of small for gestational age fetuses (EESl 1000 mg/kg). In addition, EES1 increased the frequency of external, visceral, and skeletal malformations. Because of the above, it is considered that EESl is not maternotoxic, does not alter reproductive performance, but does alter embryofetal development. Its use in the gestational period is not indicated due to its teratogenic potential.